Refuge in the Bosoms of the Mountains: A Ninth-Century Muslim Appraisal of Monastic Piety - Bowman, Brad (Islam and Christian-Muslim relations, 2019)
This article examines a relatively little-known text, the Kitāb al-ruhbān/Book of Monks, from the ninth-century Muslim moralist, Ibn Abī al-Dunyā. The topical range of Ibn Abī al-Dunyā's own literary corpus was extensive, yet the concern for ascetic practices forms a consistent thread throughout his work. As for this particular text, the esoteric wisdom associated with asceticism is specifically communicated through the teachings of Christian hermits. The Kitāb al-ruhbān, formulated as a collection of short dialogues and edifying statements regarding Christian monastic piety, profoundly demonstrates the continuing appreciation for monastic insight, particularly amongst Muslim ascetics, well into the Islamic period. There are, moreover, no explicit traces of sectarianism or confessional barriers here. Instead, the sagacious maxims for maintaining a righteous life are often passed from Christian hermits to devout Muslim listeners. This text thus further reveals the intricate connections between Christian monastic communities and medieval Islamic mystical culture.